Basis of Breeding and Performance of Local Barbary sheep at Slug region, Libya (Albayan Scientific Journal, 2023)
The objectives of this study were to determine the system of breeding and the basis of selection and culling and to evaluate the reproductive and production traits of local Barbary sheep at Slug region. Thirty herds were investigated and the traits studied included: herd size, breeding system, basis of selection and culling, age of ewes and rams at first breeding, stay ability of ewes and rams, yearly production/100 ewes, the percentages of death, weaning, and twinning. Weights were taken for 30 lambs in 3 herds at birth (BW) and weaning (WW) and gain in weight (GW)and daily weight gain (DWG) were calculated. Results showed inbreeding was common among 46.7 of herd owner and selection of rams was based on phenotype, reproductive efficiency, and pedigree, whereas culling based on aging and decrease of reproductive efficiency. However, ewes were selected on the basis of phenotype and culled on the basis aging, sterility and diseases. Herd size was 284 head on average and rams were used at first mating at age 9.7 month and ewes at age 12.8 month on average. One ram was used to bred 26 ewes on average. Longevity of rams and ewes was too long 11 and 9 years, respectively. The percentages for death Mortality percentage, weaning, and twinning were 5.1, 85.2, and 7.7, respectively. Variation were observed on BW, WW, GW and DWG and their means were 4.24 kg, 23.66 kg, 19.38 kg, and 176.20 gm, respectively. Performance of Barbary sheep might be improved through cooperative breeding program, establishing test station for selection and lowering stay ability of rams and ewes.
Keywords: Libyan Barbary sheep; Basis of Breeding; birth and weaning weight; yearly Production; Slug.